ISOLASI DAN IDENTIFIKASI BAKTERI PENGHASIL ENZIM GELATINASE DI MUARA PANTAI LUBUK TUKKO TAPANULI TENGAH - Purba, Gusmita Enda Lorenza; Rasyidah, Rasyidah; Mayasari, Ulfayani (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
Gelatinase enzyme is an enzyme that plays an important role in the food and non- food industries. Gelatinase enzymes can come from animals, plants and microorganisms. This study aims to determine whether there are bacteria that produce gelatinase enzymes, and the characterization of gelatinase enzyme-producing bacteria found in the estuary of Lubuk Tukko Beach, Tapanuli Tengah. The research was carried out from September to November 2021 at UPT Laboratorium Mikrobiologi Kesehatan Daerah Jl. Williem Iskandar, Medan. This research was divided into several stages, namely isolation and inoculation, gelatin test, gram stain test, dan biochemical test. Isolation of bacteria found 15 pure isolates and it was known that seven of the pure isolates were bacteria producing gelatinase enzymes with isolate codes SS141, SS144, SS241, SS342, SS353, SS361 and SS363. The results obtained were characterized by gram staining and biochemical tests and obtained the results of 1 bacterial isolate of the genus Micrococcus with code SS361 and other bacterial isolates of the genus Bacillus.